Reducing Smoking-related Morbidity and Mortality in Kalaallit Nunaat (Greenland) - Glover, Marewa (Zenodo, 2019)
A submission on the Naalakkersuisut Ministry of Health draft parliamentary Act on tobacco products and non-smoking environments (the Smoking Act). Adopting a tobacco harm reduction approach that is tailored for the specific needs of the indigenous people of Greenland. : The work of the Centre of Research Excellence: Indigenous Sovereignty & Smoking is supported by a grant from the Foundation for a Smoke-Free World, an independent nonprofit organization whose purpose is to improve global health by ending smoking in this generation. The Foundation has a pledge agreement with Philip Morris International (PMI) that secures funding and ensures complete autonomy to pursue its mission to end smoking in this generation. PMI and the tobacco industry, generally, are precluded from having any control or influence over how the Foundation spends its funds or focuses its activities. Independence is explicitly outlined in the Foundation's bylaws. The research produced by the Centre of Research Excellence: Indigenous Sovereignty & Smoking, the contents, selection and presentation of facts, as well as any opinions expressed on the Centre's website, or in its presentations and publications are the sole responsibility of the Centre and its authors and under no circumstances shall be regarded as reflecting the position of the Foundation for a Smoke-Free World, Inc.